In situ thermal ablation augments antitumor efficacy of adoptive T cell therapy. (29th November 2019) - Ito, Fumito; Vardam, Trupti D.; Appenheimer, Michelle M.; Eng, Kevin H.; Gollnick, Sandra O.; Muhitch, Jason B.; Evans, Sharon S.
Abstract: Purpose: The aim of this study is to investigate whether radiofrequency ablation (RFA) improves the efficacy of adoptive T cell immunotherapy in preclinical mouse cancer models. Method: Mice implanted subcutaneously ( sc ) with syngeneic colon adenocarcinoma or melanoma were treated with sub-curative in situ RFA (90 °C, 1 min). Trafficking of T cells to lymph nodes (LN) or tumors was quantified by homing assays and intravital microscopy (IVM) after sham procedure or RFA. Expression of trafficking molecules (CCL21 and intercellular adhesion molecule-1 [ICAM-1]) on high endothelial venules (HEV) in LN and tumor vessels was evaluated by immunofluorescence microscopy. Tumor-bearing mice were pretreated with RFA to investigate the therapeutic benefit when combined with adoptive transfer of in vitro -activated tumor-specific CD8 + T cells. Results: RFA increased trafficking of naïve CD8 + T cells to tumor-draining LN (TdLN). A corresponding increase in expression of ICAM-1 and CCL21 was detected on HEV in TdLN but not in contralateral (c)LN. IVM revealed that RFA substantially enhanced secondary firm arrest of lymphocytes selectively in HEV in TdLN. Furthermore, strong induction of ICAM-1 in tumor vessels was associated with significantly augmented trafficking of adoptively transferred in vitro -activated CD8 + T cells to tumors after RFA. Finally, preconditioning tumors with RFA augmented CD8 + T cell-mediated apoptosis of tumor targets and delayed growth of established tumors when combined with adoptive T cell transfer immunotherapy. Conclusions: These studies suggest that in addition to its role as a palliative therapeutic modality, RFA may have clinical potential as an immune-adjuvant therapy by augmenting the efficacy of adoptive T cell therapy.